2015
DOI: 10.1002/cplx.21731
|View full text |Cite
|
Sign up to set email alerts
|

Results of a beer game experiment: Should a manager always behave according to the book?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Moreover, the three studies adopting a four-echelon structure (see, e.g., [37,40,45,53]) do not provide specific insights on the dynamics of SC under demand information sharing with delays/ errors (in the following, demand delays/errors).…”
Section: Inmentioning
confidence: 99%
“…Moreover, the three studies adopting a four-echelon structure (see, e.g., [37,40,45,53]) do not provide specific insights on the dynamics of SC under demand information sharing with delays/ errors (in the following, demand delays/errors).…”
Section: Inmentioning
confidence: 99%
“…We present the equations of the simplified version below (see Sterman (1989) and Edali and Yasarcan (2016) for an extended version).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, the research has been more focused on how to minimize this bullwhip effect with various inventory management techniques and strategies. 68 Simulation modeling is the primary method for analyzing the dynamics of a supply chain. 9 However, a literature review we conducted revealed that the work done for this purpose lacked either the complexity of the supply chain model or the results found were unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The research that is most similar to our case is that of Edali and Yasarcan. 8 The authors built a system dynamics model of the beer game supply chain and conducted a series of experiments with the aim of minimizing the bullwhip effect. The model decides on order sizes according to a dynamic decision-making heuristic, so that the order size varies at each turn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation